Antimicrobial susceptibility of uropathogens isolated from Cambodian children - Moore, C; Sona, S; Poda, S; Putchhat, H; Kumar, V; Sopheary, S; Stoesser, N; Bousfield, R; Day, N; Parry, C (Taylor and Francis, 2016)

(untitled)
Background: Bacterial resistance to commonly used antimicrobials is an increasing problem in Asia but information concerning the antimicrobial susceptibility of bacteria causing urinary tract infections (UTIs) in children is limited. Methods: This was a 5-year retrospective study of children with suspected UTI attending a paediatric hospital in north-west Cambodia. Urines with a positive culture containing a single organism with a count of >105 colony-forming units (CFU)/ml were considered diagnostic of infection. The organism was identified and the resistance pattern (using CLSI guidelines) and presence of an extended-spectrum β-lactamase (ESBL) phenotype was determined. Results: In total, there were 217 episodes of infection, 210 (97%) with Gram-negative bacteria. Escherichia coli was the most common infecting isolate with high levels of resistance to most oral antibiotics, except nitrofurantoin. Nearly half of the E. coli (44%) were extended-spectrum cephalosporin (ESC)-resistant with the proportion increasing significantly over the 5-year period. ESC-resistant E. coli were more likely to be multi-drug-resistant and 91% demonstrated an ESBL phenotype. Conclusion: The data highlight the importance of microbiological surveillance of UTIs in children, particularly in areas where there are known to be multiply resistant organisms.